Kampung boy : yesterday & today - Lat Dato' 1951- (MPH Group Publishing, 2014)
The Kampung Boy tells the story of a young boy, Lat, and his childhood in a kampung (village). The story opens with his birth in a kampung in Perak, Malaysia, and the traditional rituals surrounding the event: the recitation of blessings, the singing of religious songs, and the observance of ceremonies. As Mat grows older, he explores the house, gradually shifting the story's focus to the comic activities of his family outside their abode.